2020
DOI: 10.1200/jco.2020.38.15_suppl.1000
|View full text |Cite
|
Sign up to set email alerts
|

KEYNOTE-355: Randomized, double-blind, phase III study of pembrolizumab + chemotherapy versus placebo + chemotherapy for previously untreated locally recurrent inoperable or metastatic triple-negative breast cancer.

Abstract: 1000 Background: Pembrolizumab (pembro) monotherapy showed promising antitumor activity and manageable safety in patients (pts) with metastatic TNBC in KEYNOTE-012, -086 and -119. KEYNOTE-355 (ClinicalTrials.gov, NCT02819518) compared pembro + chemotherapy (chemo) vs placebo (pbo) + chemo for previously untreated locally recurrent inoperable or metastatic TNBC. Methods: Pts with ≥6 mo DFI were randomized 2:1 to pembro + chemo (nab-paclitaxel; paclitaxel; or gemcitabine/carboplatin) or pbo + chemo for up to 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(155 citation statements)
references
References 0 publications
3
143
0
9
Order By: Relevance
“…Patients with metastatic or locally advanced TNBC with PD-L1 expression on immune cells occupying ≥1% of tumor area have demonstrated survival benefit with combined therapy of Atezolizumab and Nab-Paclitaxel [46]. Similar results were obtained recently with Pembrolizumab, confirming that patients expressing PD-L1 obtain better outcomes [47]. Moreover, it has been shown that PD-L1 expression remains largely unaltered after neoadjuvant chemotherapy [48,49], raising the possibility that adjuvant immune checkpoint inhibitor therapy could improve survival in this patient population.…”
Section: Heterogeneity In Target Expressionsupporting
confidence: 64%
“…Patients with metastatic or locally advanced TNBC with PD-L1 expression on immune cells occupying ≥1% of tumor area have demonstrated survival benefit with combined therapy of Atezolizumab and Nab-Paclitaxel [46]. Similar results were obtained recently with Pembrolizumab, confirming that patients expressing PD-L1 obtain better outcomes [47]. Moreover, it has been shown that PD-L1 expression remains largely unaltered after neoadjuvant chemotherapy [48,49], raising the possibility that adjuvant immune checkpoint inhibitor therapy could improve survival in this patient population.…”
Section: Heterogeneity In Target Expressionsupporting
confidence: 64%
“…nab-paclitaxel, paclitaxel or gemcitabine/carboplatin), compared to placebo plus chemotherapy (KEYNOTE-355 Phase III trial, NCT02819518). A significant PFS benefit with the pembrolizumab-chemo combination in patients whose tumors expressed PD-L1 (CPS ≥10) was reported (9.7 vs. 5.6 months for chemotherapy alone) (34). The study is currently in progress to evaluate OS, the other primary endpoint of the trial.…”
Section: Investigational Drugsmentioning
confidence: 99%
“…Since atezolizumab in combination with nab-paclitaxel is already licensed in the first treatment line for patients with metastatic breast cancer, the results of the KEYNOTE-355 study, which tests the PD-1 antibody pembrolizumab also in the first treatment line, have also been published 45 .…”
Section: Treatment Of Patients With Advanced Tnbc or Brca-associated mentioning
confidence: 99%
“…Die KEYNOTE-355-Studie hat Patienten mit fortgeschrittenen TNBC eingeschlossen, die im metastasierten Stadium noch keine Vorbehandlung hatten. Verglichen wurde eine Kombination aus Chemotherapie und Pembrolizumab mit einer alleinigen Chemotherapie 45 . Als Chemotherapie konnte eingesetzt werden: nab-Paclitaxel, Paclitaxel oder Gemcitabin/Carboplatin.…”
Section: Immuntherapienunclassified
See 1 more Smart Citation